Sintering Behavior of Lampung Limestone-Based Hydroxyapatite for Use as a Bone Filler Material - Saputra, Rizal Adi; Sukmana, Irza; Hendriyanto, Agus; Riszal, Akhmad; Hendronursito, Yusup; Wicaksono, Mahruri Arif (FTMD Institut Teknologi Bandung, 2024)
Limestone from Mount (Mt.) Beranti, Lampung Province, contains 97.43% calcium carbonate (CaCO₃), making it a suitable natural precursor for synthesizing hydroxyapatite (HA). HA is widely utilized as a bone tissue filler, particularly in treating osteoporosis. In this study, CaCO₃ was processed using ball milling at 300 rpm for durations of 2, 3, and 4 hours, followed by sintering at temperatures of 600°C, 800°C, and 1000°C for holding times of 2, 3, and 4 hours. FTIR analysis using the hydrothermal method on calcined limestone powder revealed characteristic peaks corresponding to phosphate (PO₄³⁻) at 1025.45 cm⁻¹, calcium oxide (Ca–O) at 1413.59 cm⁻¹, and hydroxyl (O–H) at 3030.33 cm⁻¹, which closely resemble those found in commercial HA. SEM-EDX analysis at 1000°C for 4 hours showed a homogenous microstructure, with EDX results indicating the highest concentrations of calcium and phosphate after milling for 2 hours. Vickers hardness testing confirmed the highest hardness value was also achieved at 1000°C for 4 hours. Overall, the FTIR, SEM-EDX, and microhardness results demonstrate enhanced properties of HA, supporting its effectiveness as a material for filling porous bone tissue. Keywords: Limestone; Hydroxyapatite (HA); Calcium Carbonate (CaCO3); Bone Filler